Effects of different wind data sources in offshore wind power assessment. (May 2015) - Soukissian, Takvor H.; Papadopoulos, Anastasios
Abstract: Currently, approximately 5.3% of electricity production in Europe comes from wind energy. The increase of the size and the improved efficiency of wind generators have permitted their utilization offshore, leading to exploitation of offshore wind energy. Although offshore wind farms are well established in northern European countries, in the Mediterranean Sea they are still in their infancy. It is expected that within the next few years, offshore wind farming will grow considerably in this area. The accurate estimation of the wind speed fields is of most importance for the assessment of offshore wind energy resources. In this work, the effects of alternative wind data sources on the wind climate analysis are examined along with the offshore wind power density estimation in four locations across the Aegean Sea. In order to develop correction relations for satellite and model wind data, taking as reference the buoy measurements, the data are analysed and calibrated using the Error-In-Variables approach. The effects of the different data sources on the wind climate analysis and the estimation of the mean wind power density before and after the calibration procedure are presented and discussed. The Error-In-Variables approach performed better and reduced significantly the uncertainties of the alternative data sources. Highlights: In-situ, model-generated and satellite wind speed data are compared and analysed. Correction relations for satellite and model-generated wind data are developed. The effects of different wind data sources on offshore wind energy are assessed. Evaluation of correction relations in terms of wind power density estimation. Quantification of the uncertainties of different wind data sources.